INCORPORATING SUSTAINED PROJECT-BASED GROUP WORK INTO THE EFL CLASSROOM: CRITICAL REFLECTIONS FROM TWO TERTIARY EFL INSTRUCTORS - Alice, S. Lee; Eve, E. Smith (PUBLISHINGS of Kostanay State Pedagogical Institute, 2014)
his paper uses critical reflection as a framework for two tertiary EFL instructors to engage in reflective practice of their professional decisions related to implementing sustained project-based group work. The authors each describe one critical incident stemming from their semester-long group work interactions with their students. They then position each incident within the larger sociocultural context of the academia and professional world in Macao. Included in this deconstruction are the assumptions each instructor brought with her into her classroom. Analyzing these assumptions together with their critical reflection allows each author to achieve a better understanding of decisions made inside and outside of their classrooms and how these decisions impact group work activities.
Keywords: critical reflection; group work